Solve this system of equations: y = x2 – 3x + 12 y = –2x + 14 1.Isolate one variable in the system of equations, if needed. y = x2 – 3x + 12 y = –2x + 14 2.Use substitution to create a one-variable equation. –2x + 14 = x2 – 3x + 12

Respuesta :

Answer:

C) {–1, 2}

Step-by-step explanation:

ed2021 got it right :)

The solution of the system are { x = 2, y = 10} or { x = -1 , y = 16}

What is equation?

Equation is the defined as mathematical statements that have a minimum of two terms containing variables or numbers is equal.

The given system of equations:

y = x² – 3x + 12

y = –2x + 14

Substitute the y = -2x + 14 into the first equation :

–2x + 14 = x² – 3x + 12

Rewrite the equation that all nonzero terms to the left side of the equation,

x² – 3x + 12 + 2x - 14 = 0  

Combine the same terms in the equation,

x² - x - 2 = 0

x²- 2x + x - 2 = 0

Factor the first two terms and the last two terms separately

x(x- 2) + 1 (x - 2) = 0

(x - 2)( x+1 ) = 0

Apply Zero Product Property

x - 2 = 0 or  x + 1 = 0

Rearrange unknown terms to the left side of the equation:

x = 2 or x = -1

Substitute the value x = 2 into the equation y = –2x + 14,

y = –2(2) + 14

y = –4 + 14

y = 10

Substitute the value x = -1 into the equation y = –2x + 14,

y = -2(-1) + 14

y = 2 + 14

y = 16

Hence, the solution of the system are { x = 2, y = 10} or { x = -1 , y = 16}

Learn more about equation here:

brainly.com/question/10413253

#SPJ5

ACCESS MORE